Case report: Dopamine Dysregulation Syndrome, mania, and compulsive buying in a patient with Parkinson's disease - Silva, Carlos; Rebelo, Marta; Chendo, Inês (Frontiers in Neurology, 2023)
Neuropsychiatric symptoms and syndromes are among the most common non-motor symptoms of Parkinson's Disease but they are frequently unrecognized and untreated. Dopamine Dysregulation Syndrome is an uncommon complication of the treatment of Parkinson's disease, characterized by an addictive use of dopamine far more than the dosage required for treatment of objective motor impairment, leading to severe dyskinesia, euphoria, aggressivity, or psychosis. We present a paradigmatic case of Dopamine Dysregulation Syndrome, Mania, and Compulsive Buying in a 55-year-old male with Parkinson's Disease. We also reviewed the risk factors and the therapeutic management of Dopamine Dysregulation Syndrome in Parkinson's Disease.